The Perceptions of Pre-service Teachers on Bachelor of Education Program in Shaheed Benazir Bhutto University, Pakistan (Journal of Social Sciences Review, 2021)
The provision of quality teachers by teacher preparation programs determines the quality of education in schools. The study aimed to define pre-service teachers' beliefs about teacher education and include recommendations for improving teacher education, given the importance of teacher education for the quality of education in educational institutions. The study included 45 pre-service teachers from Shaheed Benazir Bhutto University's education department in Dir Upper, Khyber Pakhtunkhwa, Pakistan. A total of 30 people were chosen for inclusion in the analysis using a purposive random sampling method. A questionnaire was developed, validated, and piloted to ensure its accuracy. The information was gathered using self-administered questionnaires and evaluated using mean ratings, standard deviation, and the chi-square significance test. The study found that pre-service teachers in the institute are satisfied with their needs and demands through teacher education, that teacher education curricula are tailored to the needs of pre-service teachers, that subject content courses are appropriate, that the scope of teaching practicum is broad, that training is linked to practical school experiences, and that school management courses are offered. The pedagogy courses help pre-service teachers improve their teaching skills, and they receive adequate training in evaluation methods. There are also quality academic research activities. The study suggested that pre-service teachers attend orientation sessions to learn about their needs and demands, which could be met through teacher preparation. Teacher education curricula are revised to provide more realistic exposure to the school's atmosphere and activities.
Keywords: Bachelor of education; beliefs; teacher education; pre-service teachers